Forest structure and carbon stocks of Osun-Osogbo sacred grove, Nigeria (2020)
Forest trees and soil are considered for climate change mitigation. Forest structure of the grove is required to predict its capacity to mitigate climate change. Therefore, the objective of this study was to determine the forest structure and carbon stocks of Osun-Osogbo Sacred grove. Five (30 × 30 m2) plots were demarcated in Old-growth forest (OF) and Re-growth forest (RF). Trees with ≥10 cm diameter-at-breast-height (dbh) were identified to species level and enumerated. Tree height and dbh were measured and stem volumes were converted to carbon stock. Soil samples were collected with cores at three soil depths, oven-dried and carbon content estimated. The tree species diversity and richness indices of OF was higher than OR. Diameter distribution of OF and RF expressed reverse J-shaped and rotated sigmoid curves, respectively. The stem carbon stock ranged from 0.12±0.00 (OF) to 0.02±0.00 Mg/ha (RF). The soil carbon stock ranged from 0.65 (OF) to 0.90 Mg/ha (RF). Stand structure of OF was more develop than RF. The OF and RF contained high stem and soil carbon stocks, respectively. Forest structure enhances stem carbon stock of Old-growth forest while soil of Re-growth forest is also an option for carbon sequestration.